Strengths and Weaknesses of Persona Creation Methods: Outlining Guidelines for Novice and Experienced Users and Opportunities for Digital Innovations - Jansen Bernard J.; Jung Soon-Gyo; Salminen Joni; Guan Kathleen W.; Nielsen Lene (United States, 2022)
Persona is a technique for enhancing user understanding and improving the user-centered design of digital products. Persona creation has traditionally been divided into Qualitative, Quantitative, and Mixed Methods approaches. However, no literature systematically contrasts the strengths and weaknesses of these approaches. We review the literature to map the strengths and weaknesses of these approaches and evaluate the potential of personas for the domain of digital innovation. We provide insights for better creation and use of personas by both researchers and practitioners, especially those that are new to personas, deploying personas in a new domain, or familiar with only one of the persona creation approaches.
The proceedings of the 54th Hawaii International Conference on System Sciences 2021